Identification of in vitro angiotensin‐converting enzyme and dipeptidyl peptidase IV inhibitory peptides from draft beer by virtual screening and molecular docking - Wenhui, Tian; Shumin, Hu; Yongliang, Zhuang; Liping, Sun; Hua, Yin (Journal of the science of food and agriculture, 2022)
BACKGROUND Hypertension and diabetes are two kinds of senile diseases which often occur simultaneously. The commonly used drugs in clinic may produce certain side effects. Food‐derived polypeptide is a kind of polypeptide with great development potential, which has many functions of regulating human physiological function. Beer is rich in nutrition but there are few researches on bioactive peptides in beer. RESULTS In this study, a rapid virtual screening method was established to obtain bioactive peptides from Tsingtao draft beer. The peptide sequence was analyzed by ultra‐performance liquid chromatography‐quadrupole‐Orbitrap‐tandem mass spectrometry (UPLC‐Q‐Orbitrap‐MS2), and 50 peptides were identified. Eight peptides with potential biological activities were screened by using Peptide Ranker software and previous literature references. On the basis of absorption prediction, toxicity prediction, and molecular docking analysis, LNFDPNR and LPQQQAQFK were finally confirmed. The molecular docking results showed that two peptides could bind angiotensin‐converting enzyme (ACE) and dipeptidyl peptidase IV (DPP‐IV) tightly by hydrogen bonding and hydrophobic interaction. The in vitro activity evaluation results showed that two peptides had obvious ACE and DPP‐IV inhibitory activity. CONCLUSION This study established a method for rapidly screening bioactive peptides from Tsingtao draft beer, screened two ACE and DPP‐IV inhibitory peptides in beer and analyzed their active action mechanism. This article may have great theoretical significance and practical value to further explore the health function of beer. © 2021 Society of Chemical Industry.